(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A baseline survey was conducted in a cluster area (279 households) of Mymensingh district in Bangladesh to know the farmers’ socio-economic condition, and overall production and husbandry practices regarding indigenous poultry farming and assess future outlook. Data were analyzed following descriptive statistics. Most of the farmers (54.84%) were in middle age type (31-50 years) and landless (41.58%). The average annual income of farmers recorded 61,260 BDT or 875 USD where agriculture (49.10%) was found as primary occupation. The average indigenous chicken (196 HHs), duck (16 HHs) and pigeon (4 HHs) distribution per household were 5.62, 3.81 and 3, respectively. Average egg production per clutch in chicken and duck identified 13.47 and 17.50 eggs, respectively, with 76.78 and 69.61% hatchability. Indigenous poultry (60.20%) housed inside the dwelling of farmers. Natural and uncontrolled breeding observed for all indigenous livestock in the studied area. Vaccination practice followed very limited for poultry while Newcastle disease found most prominent in poultry (65.82%). Proper initiative, funding, farm-based training to educated farmers including modern animal husbandry practices could increase indigenous poultry population and consequent profit. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 557-563